Role of CT in the Evaluation of Nasopharyngeal Angiofibroma in Para Nasal Sinus - Islam, T; Rahman, M; Nabi, S; Khondker, L; Sultana, S (Bangladesh Medical Journal, 2014)
Computed tomography (CT) is the gold standard for exact delineation of paranasal sinus(PNS) disease. There are many radiologically important diseases of paranasal sinuses. Objective of the study was to evaluate the role of computed tomographic image(CT) in the diagnosis of nasopharyngeal angiofibroma. A cross sectional study was carried out in the department of Radiology & Imaging, Bangabandhu Sheikh Mujib Medical University(BSMMU), Dhaka in collaboration with department of Otolaryngology and department of Pathology of BSMMU. This study was carried out with patients having suspected PNS mass and the duration of the study was from January 2009 to October 2010. Maximum 30.3% patients were belonged to 46 to 60 years age group and of them maximum 73.7% had complaints of nasal obstruction. Maximum 53.9% patients had PNS mass in maxillary sinuses and out of all cases 8 were diagnosed as having nasopharyngeal angiofibroma by CT scan and confirmed by histopathological evaluation. Two cases were diagnosed as having nasopharyngeal angiofibroma by CT scan but not confirmed by histopathological findings. By CT evaluation total 66 cases were diagnosed as having other than nasopharyngeal angiofibroma and confirmed by histopathology. Sensitivity of CT scan to diagnose nasopharyngeal angiofibroma was 100.0%, specificity 97.1 %, positive predictive value 80.0%, negative predictive value 100.0% and accuracy 97.4%. In conclusion, CT scan of the nasopharyngeal angiofibroma in para nasal sinus provides more information and better image quality and CT diagnosis correlate well with the findings of histopathology. DOI: http://dx.doi.org/10.3329/bmj.v41i2.18801 Bangladesh Medical Journal 2012 Vol. 41 No. 2: 27-30